(untitled) (Archives of Pediatrics of Uruguay, 2020)
Introduction: acute gastroenteritis (AGE) is a prevalent disease in childhood. The AGE National Guidelines were published in 2014 in Uruguay, but there are no studies assessing its compliance. Objectives: to determine the degree of compliance with the AGE therapeutic guidelines for the case of children of under 3 years of age admitted at the Pereira Rossell Hospital Center during 2015-2017. Materials and methods: descriptive, retrospective study. All children under 3 years of age hospitalized for AGE were included. Variables: age, hydration level at admission, contraindication for oral administration treatments. Compliance with recommendations was evaluated by comparing the recommended behavior with the one actually adopted in each case, in general and specifically regarding three aspects: hydration plan; nutritional and antimicrobial prescription. Compliance was classified as: good >80%, acceptable 79-60, bad <60%. Results: 487 children were hospitalized for AGE, median age 10.7 months; dehydrated 59% (289), mild (59), moderate (193), severe (37); with contraindication of oral administration 39%. Intravenous hydration therapy (IVHT) was prescribed for 44.5% of children without oral contraindication. Overall compliance with national recommendations was 77%: hydration plan 76%, (children without dehydration 86%, with dehydration: mild 69%, moderate 70% and severe 65%); nutritional plan 82% and antimicrobial prescription 72%. Conclusions: global compliance with the recommendations was acceptable. However, some areas for improvement were identified: IVHT should be reserved for situations where there is contraindication to the oral / enteral route and the recommended dosage and infusion time should be respected.